Slow-release L-cysteine capsule prevents gastric mucosa exposure to carcinogenic acetaldehyde: results of a randomised single-blinded, cross-over study of Helicobacter-associated atrophic gastritis. (1st February 2017) - Hellström, Per M.; Hendolin, Panu; Kaihovaara, Pertti; Kronberg, Leif; Meierjohann, Axel; Millerhovf, Anders; Paloheimo, Lea; Sundelin, Heidi; Syrjänen, Kari; Webb, Dominic-Luc; Salaspuro, Mikko
Abstract: Introduction: Helicobacter -induced atrophic gastritis with a hypochlorhydric milieu is a risk factor for gastric cancer. Microbes colonising acid-free stomach oxidise ethanol to acetaldehyde, a recognised group 1 carcinogen. Objective: To assess gastric production of acetaldehyde and its inert condensation product, non-toxic 2-methyl-1, 3-thiazolidine-4-carboxylic acid (MTCA), after alcohol intake under treatment with slow-release L-cysteine or placebo. Methods: Seven patients with biopsy-confirmed atrophic gastritis, low serum pepsinogen and high gastrin-17 were studied in a cross-over single-blinded design. On separate days, patients randomly received 200 mg slow-release L-cysteine or placebo with intragastric instillation of 15% (0.3 g/kg) ethanol. After intake, gastric concentrations of ethanol, acetaldehyde, L-cysteine and MTCA were analysed. Results: Administration of L-cysteine increased MTCA ( p  < .0004) and decreased gastric acetaldehyde concentrations by 68% ( p  < .0001). The peak L-cysteine level was 7552 ± 2687 μmol/L at 40 min and peak MTCA level 196 ± 98 μmol/L at 80 min after intake. Gastric L-cysteine and MTCA concentrations were maintained for 3 h. The AUC for MTCA was 11-fold higher than acetaldehyde, indicating gastric first-pass metabolism of ethanol. With placebo, acetaldehyde remained elevated also at low ethanol concentrations representing 'non-alcoholic' beverages and food items. Conclusions: After gastric ethanol instillation, slow-release L-cysteine eliminates acetaldehyde to form inactive MTCA, which remains in gastric juice for up to 3 h. High acetaldehyde levels indicate a marked gastric first-pass metabolism of ethanol resulting in gastric accumulation of carcinogenic acetaldehyde. Local exposure of the gastric mucosa to acetaldehyde can be mitigated by slow-release L-cysteine capsules.